Incidence and Outcome of Pediatric Patients With Intracranial Hemorrhage While Supported on Ventricular Assist Devices. Issue 1 (21st November 2013) - Niebler, Robert A.; Lew, Sean M.; Zangwill, Steven D.; Woods, Ronald K.; Mitchell, Michael E.; Tweddell, James S.; Ghanayem, Nancy S.
Abstract Pediatric patients supported on ventricular assist devices (VADs) require systemic anticoagulation and are at risk for intracranial hemorrhage (ICH). Little is known about the incidence or outcomes of pediatric patients with ICH while supported on a VAD. A retrospective chart review of all patients receiving VAD support was completed. Patients diagnosed with ICH while supported on a VAD were identified. Significant factors prior to diagnosis of ICH, medical/surgical treatment of ICH, and patient outcomes were assessed. Five of 30 (17%) patients supported on a VAD from January 2000 to November 2012 were diagnosed with an ICH. Four patients had an identified cerebral thromboembolic injury prior to the ICH. Four patients required interruption in their anticoagulation regimen due to other bleeding concerns prior to ICH. Neurosurgical intervention consisted of evacuation of hemorrhage in one, whereas two others required management of hydrocephalus with external ventricular drainage. Three of the five patients died on VAD support. Two deaths were directly related to ICH, whereas the third was unrelated. Two patients were successfully transplanted; one remains with a significant neurological impairment, and the other has recovered with minimal residual impairment following neurosurgical evacuation of a large subdural hematoma. ICH is a devastating complication of VAD support. Prior ischemic infarcts and interruptions to anticoagulation may put a patient at risk for ICH. Prompt neurosurgical evaluation/intervention can result in positive outcomes.